Validity and reliability assessment of the transformative learning outcomes and processes (TROPOS) survey in public sector work-related learning - Viterouli, Mary; Belias, Dimitrios; Koustelios, Athanasios; Tsigilis, Nikolaos (Serbian Journal of Management, 2025)
As corporate contexts and business environments become increasingly complex, Transformative Learning (TL) in workplace research is gaining prominence. This type of learning can shift perspectives, leading to psychological, convictional, and behavioural changes, as described by Clark’s (1991) adaptation of Mezirow’s theory of transformation (1978). The Transformative Outcomes and Processes Survey (TROPOS), developed by Robert Cox (2017), is a reliable tool for measuring TL, featuring four subscales: Social Support, Attitude toward Uncertainty, Criticality, and Transformative Outcomes. This study assesses the validity and reliability of the 30-item TROPOS instrument in workplace learning using a quantitative, questionnaire-based approach. Convenience sampling was employed, targeting accessible respondents from 238 employees of the Public Employment Services in Greece. Results from confirmatory factor analysis and Cronbach’s alpha confirm the instrument’s applicability to workplace learning. The study validates TROPOS as a useful tool for evaluating TL outside educational settings and extends the understanding of TL in work-related contexts. The implications and constraints of TL research are discussed, contributing to the literature and practice in this field.
Keywords: transformative learning; workplace learning; human resources development; public sector; validity and reliability